Ionospheric propagation effects for UHE neutrino detection with the lunar Cherenkov technique - McFadden, R.; Ekers, Ronald; Bray, J. (2011)
Lunar Cherenkov experiments aim to detect nanosecond pulses of Cherenkov emission produced during UHE cosmic ray or neutrino interactions in the lunar regolith. Pulses from these interactions are dispersed, and therefore reduced in amplitude, during propagation through the Earth's ionosphere. Pulse dispersion must therefore be corrected to maximise the received signal to noise ratio and subsequent chances of detection. The pulse dispersion characteristic may also provide a powerful signature to determine the lunar origin of a pulse and discriminate against pulses of terrestrial radio frequency interference (RFI). This characteristic is parameterised by the instantaneous Total Electron Content (TEC) of the ionosphere and therefore an accurate knowledge of the ionospheric TEC provides an experimental advantage for the detection and identification of lunar Cherenkov pulses. We present a new method to calibrate the dispersive effect of the ionosphere on lunar Cherenkov pulses using lunar Faraday rotation measurements combined with geomagnetic field models.